Walter Rosene bird calendar, Boone County, 1928-1937 - Rosene, Walter, 1880-1941et al (1928)
A ten year calendar of three hundred and eighty-one wild birds of Iowa annotated by Walter Rosene with sighting dates of species located in Boone County for the years 1928 through 1937. Also includes a record of three birds of North America not included in the Iowa list that were observed by Rosene. Epson - sheet feed